A CASE REPORT OF ACUTE NONTRAUMATIC SPONTANEOUS SUBDURAL HAEMATOMA DUE TO PSEUDOANEURYSM OF MIDDLE MENINGEAL ARTERY - Makkiyah, Feda; Nurrahmah, Rahma Nida (MNJ (Malang Neurology Journal), 2021)
Acute subdural bleeding is blood collection in subdural space, usually caused by laceration of the bridging vein that runs from cortex to meningeal layer. On the other hand, the acute epidural hematoma is a collection of blood above the dura mater, usually caused by tearing of the middle meningeal artery. Subdural hematoma acute more likely happen in elderly than young adult. This case report discusses acute spontaneous subdural hematoma that was caused by a pseudoaneurysm of the middle meningeal artery. Seventeen years old boy came with symptoms of high intracranial pressure because of massive subdural bleeding. He was undergone craniotomy. After the clot removal operation, Digital Subtraction Angiography revealed vascular blush and pseudoaneurysm of the middle meningeal artery. Onyx embolization was delivered to proximal to a distal branch of the middle meningeal artery. The patient recovered in good condition, and no rebleeding in two years. Conclusion. Acute spontaneous subdural bleeding even though it is quite rare, but the chance of fatal rebleeding is high. As a result, one still has to look for the source of bleeding and manage comprehensively with embolization.